Pekerja Seks Komersial: Pengetahuan, Persepsi, dan Perilaku Pencegahan Penularan Infeksi Menular Seksual (IMS) di Kota Semarang - Matahari, Ratu; Shaluhiyah, Zahroh (Jurnal Promosi Kesehatan Indonesia, 2013)
Perception is essentially a cognitive process experienced by everyone to understand information about its environment, either through the senses of sight, hearing, feeling, living, and smell. Sexually Transmitted Infections (STI) developed prior to the spread of HIV & AIDS through sexual behavior (having sex) with multiple partners, both heterosexual and homosexual. The purpose of this study was to understand the female sex workers’ knowledge of STIs, their perceived vulnerability, severity, and prevention behavior of STIs transmission.  The study was conducted using a qualitative approach. The method used in this study is the in depth interviews (in-depth interviews) in 3 commercial sex workers suffer from IMS and two group discussions (FGDs) and interviews with informants triangulation is pimp at Sunan Kuning brothel in Semarang.  Perceptions of vulnerability to female sex workersabout prevention of STIs has been good as well as the perception of the seriousness of the commercial sex workers for STIs has also been good. However, STI prevention behaviors they are still not good. It is evident that they still believe the myths that  developed in the communityabout how that is believed to prevent the transmission of STIs.